2005
DOI: 10.1152/ajpheart.00073.2005
|View full text |Cite
|
Sign up to set email alerts
|

A role for T lymphocytes in mediating cardiac diastolic function

Abstract: The induction of T helper (TH) lymphocytes by distinct TH ligands results in a differentiation to TH1/TH2 subsets based on their unique pattern of cytokine secretion and effector functions. We hypothesized that the relative proportion of TH1/TH2 directly relates to cardiac fibroblast (CF) function and thereby cardiac extracellular matrix (ECM) composition and cardiac diastolic function in the absence of injury or altered wall stress. We compared the effect of selective TH1 with TH2 inducers on cardiac gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
67
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 57 publications
6
67
1
Order By: Relevance
“…Femalecats exhibited a reduction of IL-1, IL-2, IL-4, IL-6, IFN-γ, MMP-3 and TIMP-2 with age,in male cats this applied for IL-6, MMP-2 and TIMP-1.Conflicting results are reported for the role of immune modulatory cytokines in cardiac remodelling. In mouse models, Th2 induction resulted in reduced ventricular stiffness, and Th1 cells were involved in initiation of fibrosis and collagen crosslinking (Yu et al, 2005;, whereasanother 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 21 study did detecta shift from Th1 to Th2 response in old mice in association with interstitial myocardial fibrosis (Cieslik et al, 2011). We observed a reduction of all three immune modulatory markers (IL-2, IL-4,IFN-γ)with age in thefemale cats, which might be consistent with a generally reduced myocardial inflammatory response, as suggested by thereduced transcriptionof IL-1 and IL-6.Aupperle and co-authors (2011) observed reduced TIMP-2 expression in association with myocardial fibrosis in cats.In older sheep (> 8 years), rat and mouse models, higher myocardial MMP-2 and reduced TIMP-2 mRNA and protein expression, as well as cardiomyocyte hypertrophy and perivascular and interstitial fibrosis, imbalanced cardiac remodelling and impaired repair was observed (Kandalam et al, 2010;Wang et al, 2010;Horn et al, 2012;Givvimani et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Femalecats exhibited a reduction of IL-1, IL-2, IL-4, IL-6, IFN-γ, MMP-3 and TIMP-2 with age,in male cats this applied for IL-6, MMP-2 and TIMP-1.Conflicting results are reported for the role of immune modulatory cytokines in cardiac remodelling. In mouse models, Th2 induction resulted in reduced ventricular stiffness, and Th1 cells were involved in initiation of fibrosis and collagen crosslinking (Yu et al, 2005;, whereasanother 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 21 study did detecta shift from Th1 to Th2 response in old mice in association with interstitial myocardial fibrosis (Cieslik et al, 2011). We observed a reduction of all three immune modulatory markers (IL-2, IL-4,IFN-γ)with age in thefemale cats, which might be consistent with a generally reduced myocardial inflammatory response, as suggested by thereduced transcriptionof IL-1 and IL-6.Aupperle and co-authors (2011) observed reduced TIMP-2 expression in association with myocardial fibrosis in cats.In older sheep (> 8 years), rat and mouse models, higher myocardial MMP-2 and reduced TIMP-2 mRNA and protein expression, as well as cardiomyocyte hypertrophy and perivascular and interstitial fibrosis, imbalanced cardiac remodelling and impaired repair was observed (Kandalam et al, 2010;Wang et al, 2010;Horn et al, 2012;Givvimani et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…7 Thus, we favor a third, and novel, explanation: that the absence of TIMP-1 may alter the anatomical distribution of activated immune cells, mitigating their immunopathological effects in the heart. A previous study has shown that activated immune cells produce and secrete MMPs to disrupt the extracellular matrix, thereby facilitating their entry into cardiac tissue 42 ; another report showed that the administration of recombinant TIMP-1 arrests the migration of immune cells in vitro. 43 Furthermore, an adenovirus-mediated increase in TIMP-1 expression also resulted in diminished CVB3-induced myocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxylproline and cross-linking assays have been described by Yu et al (45). Hydroxylproline levels were quantified by comparison to a standard colorimetric curve of trans-hydroxylproline (Sigma).…”
mentioning
confidence: 99%
“…The isolation and culture of cardiac fibroblasts were performed as described by Yu et al (45). At 80 -90% confluence, cardiac fibroblasts were treated with 10 ng/ml rIL-18, 1:10 diluted supernatants from splenic T lymphocytes (described below), or 10 g/ml CpG 1668.…”
mentioning
confidence: 99%
See 1 more Smart Citation